Exploratory factorial model of collaboration in the COVID-19 era - García Lirios, Cruz (Revista MATUA, 2024)
The pandemic impacted the educational systems through anti-COVID-19 policies that are based on the distancing and confinement of people. In this sense, academic collaboration has been reported by the literature from 2019 to 2022 as an asynchronous Internet user strategy. It is a dual factorial structure that explains entrepreneurship and innovation, but does not anticipate scenarios of high risk and intensive use of Internet technologies, devices and networks in synchronous or asynchronous mode. Therefore, the objective of the study was to establish an explanatory model of the impact of the pandemic on academic collaboration. A cross-sectional, psychometric and exploratory study was carried out with a sample of 177 women from a municipality in central Mexico, considering their participation in social services and professional practices. A structure of four factors was found: Internet user, face-to-face, synchronous and asynchronous, which explained the total variance. In reference to the state of the art that exalts a two-factor model, its extension is recommended to anticipate scenarios of increasing risk.